European Biometric Border System, Securitization and (Im)mobilities in West Africa - Iwuoha, Victor; Edgar, Alistair D. (Alternatives: Global, Local, Political, 2026)
This article interrogates the European biometric ID system and securitisation measures in West African borders which have become detrimental to, first, African migrants and, second, both African and European security objectives. Using the Niger’s experience, we demonstrate how migrants’ identity problems as well as their atomisation and loosening of their social integration are directly linked to the criminalising and dehumanising border security practices they now face. This article reveals the multiple forms and effects of the unimpeded European biometric/digital control over African territorial borderlands and (im)mobilities. First is the subversion of African states’ administrative, decisional, sovereign and territorial prerogatives by way of enacting digital territorial borderscapes that enforce migrants’ identity de(re)construction. Second, the use of ‘biometric power’ to facilitate a specific modality of neoliberal biometric power relations which perpetuates global inequalities in biometric identification and (im)mobility governance. Lastly, migrants’ recourse to agentic mechanisms to contest the European biometric ID system, via discoveries and implantation of parallel border routes.